The Effect Of Screen Time On Speech Delay In Children Aged 2–6 Years At The NTB Provincial General Hospital - Saskia Nasywa Salsabila; Titi Pambudi Karuniawaty; Ni nyoman Geriputri (International Journal of Health Engineering and Technology, 2026)
The increasing use of digital devices has raised concerns about the impact of excessive screen time on children's speech and language development. This study aimed to determine the association between screen time and speech delay among children aged 2–6 years at the Child Growth and Development Clinic of West Nusa Tenggara Provincial Hospital. A cross-sectional study was conducted involving 34 children. Data were collected using parent-administered questionnaires, while child development was assessed using the Denver Developmental Screening Test II (Denver II). Statistical analysis was performed using the Chi-square test and Fisher’s Exact test. Of the participants, 58.8% had high screen time exposure, and speech and language was the most frequently affected developmental domain (82.4%). However, no significant association was found between screen time and speech delay (p = 0.172). Likewise, daily screen time exposure and parenting patterns were not significantly associated with speech delay (p > 0.05). In conclusion, screen time was not significantly associated with speech delay among children aged 2–6 years in this study population.